2019
DOI: 10.1128/aem.00018-19
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Subsurface Pressure Stimulates Metabolic Plasticity in Shale-Colonizing Halanaerobium spp

Abstract: Bacterial Halanaerobium strains become the dominant persisting microbial community member in produced fluids across geographically distinct hydraulically fractured shales. Halanaerobium is believed to be inadvertently introduced into this environment during the drilling and fracturing process and must therefore tolerate large changes in pressure, temperature, and salinity. Here, we used a Halanaerobium strain isolated from a natural gas well in the Utica Point Pleasant formation to investigate metabolic and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 75 publications
1
28
0
Order By: Relevance
“…H. congolense is anaerobic, has an optimal growth temperature of 42 C and optimal salinity concentration range of 10-15% (Ravot et al 1997), coinciding with many subsurface reservoir conditions where it is frequently found. The observation of this organism in unconventional hydraulically fractured reservoirs has been previously reported (Booker et al 2019;Daly et al 2016;Mouser et al 2016). Indigenous organisms are not likely in unconventional reservoirs due to the lack of nutrient flux within low permeability shale and minimal accommodation in shale organic porosity, which supports the hypothesis that these organisms are introduced by oil and gas drilling and production activities.…”
Section: Genomic Potential For Sporulationsupporting
confidence: 74%
“…H. congolense is anaerobic, has an optimal growth temperature of 42 C and optimal salinity concentration range of 10-15% (Ravot et al 1997), coinciding with many subsurface reservoir conditions where it is frequently found. The observation of this organism in unconventional hydraulically fractured reservoirs has been previously reported (Booker et al 2019;Daly et al 2016;Mouser et al 2016). Indigenous organisms are not likely in unconventional reservoirs due to the lack of nutrient flux within low permeability shale and minimal accommodation in shale organic porosity, which supports the hypothesis that these organisms are introduced by oil and gas drilling and production activities.…”
Section: Genomic Potential For Sporulationsupporting
confidence: 74%
“…Although carbon was not limited in our experiments, we observed significantly higher abundances of the universal stress protein (uspA, 10238) in surfactant amended cultures ( Supplementary File 4). Moreover, in a recent study on a closely-related Halanaerobium strain isolated from the same natural-gas well (H. congolense WG8), the methylglyoxal bypass was initiated under growth at high pressures with glucose as the sole carbon source, possibly to dispose of excess reducing equivalents [48]. Here, we propose cometabolism of glycols occurs either through cellular stress and/or high concentrations of glycols within the medium, activating both the methylglyoxal bypass and the propanediol dehydratase pathways.…”
Section: Surfactant Degradation Observed In Isolate Culturesmentioning
confidence: 77%
“…2a). Although there is currently no characterized enzyme for the biotransformation of PPGs under anaerobic conditions, propylene glycol, the monomer of PPGs, can be degraded by a diol dehydratase under both aerobic and anaerobic conditions, generating propionaldehyde, n-propanol, propionate, and acetone as products [33,[47][48][49]. We therefore mined metagenomes from Utica-Point Pleasant produced fluid samples for genes encoding enzymes known to degrade polyglycols to determine whether the aforementioned microbial biotransformation pathway existed in this system.…”
Section: Metagenomic Identification Of Surfactant Degrading Genesmentioning
confidence: 99%
“…Metabolic pathway analyses have revealed that Halanaerobium species have the potential for thiosulfate reduction, acid production and biofilm formation (Lipus et al, 2017), potentially making this a highly problematic microorganism during shale gas extraction. Indeed this ability has led to an emerging interest in the role that Halanaerobium species may have in the biogenesis of sulfide and corrosive organic acids, such as acetate (Booker et al, 2017(Booker et al, , 2019. It is therefore unsurprising that Halanaerobium spp.…”
Section: Persistent Sulfidogenic Taxamentioning
confidence: 99%
“…Additionally, the formation of microbial biofilms may impede gas flow and result in fracture clogging (Bottero et al, 2010). Evidence suggests that organic chemicals used during hydraulic fracturing may stimulate these deleterious processes, for example via organic acid production from fermentation reactions, and sulfide production from sulfate and thiosulfate reduction pathways (Struchtemeyer et al, 2011;Liang et al, 2016;Booker et al, 2017Booker et al, , 2019Nixon et al, 2017;Evans et al, 2019). Sulfate-reducing bacteria (SRB) have been identified previously in production fluids through next generation sequencing but their in situ role in sulfide production is undetermined (Davis et al, 2012;Struchtemeyer and Elshahed, 2012;Liang et al, 2016), whereas TRB have been isolated from these environments and represent an alternative route to sulfide production (Ravot et al, 1997(Ravot et al, , 2005Liang et al, 2016;Booker et al, 2017;Lipus et al, 2017).…”
Section: Introductionmentioning
confidence: 99%